The Loan Fee Anomaly: A Short Seller’s Best Ideas - Engelberg, Joseph E.; Evans, Richard B.; Leonard, Greg; Reed, Adam V.; Ringgenberg, Matthew C. (Management Science, 2025)
We find that equity loan fees, which have been largely ignored by the anomalies literature, are the best predictor of cross-sectional returns. When compared with 102 other anomalies and other short-selling measures, the loan fee anomaly has the highest monthly long-short return (4.01%), the highest monthly Sharpe Ratio (0.66), and, unlike other anomalies, exhibits strong persistence throughout the sample. Although prior work has shown that existing anomalies reside in high loan fee stocks, we find that 42% of loan fee outperformance is due to unique information not contained in other anomalies. Future papers that examine cross-sectional predictors of returns should include the single most effective predictor: loan fees. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.00152 .